Optimization of fermentation conditions for production of D-lactic acid with high optical purity by Lactobacillus delbrueckii HB49-2 - WANG Tong, LIU Lan, LI Peng, DENG Tao, YUE Siyuan, NIE Junhui, HUANG Xiaoping (Zhongguo niangzao)
Using Lactobacillus delbrueckii HB49-2 with high optical purity D-lactic acid production as original strain and D-lactic acid yield as the evaluation index, the fermentation conditions of high optical purity D-lactic acid produced by L. delbrueckii HB49-2 were optimized by single factor tests and response surface tests, and the optical purity of D-lactic acid was calculated. The results showed that the optimal fermentation conditions for the production of D-lactic acid by L. delbrueckii HB49-2 were inoculum 15%, fermentation temperature 39 ℃, and the optimal fermentation medium were glucose 110 g/L, peptone 10 g/L, yeast extract 10 g/L, dipotassium hydrogen phosphate 0.25 g/L, potassium dihydrogen phosphate 0.25 g/L, sodium acetate 0.05 g/L, magnesium sulfate 0.5 g/L, vitamin B12 40 mg/L, and calcium carbonate 50 g/L. After 72 h of cultivation under these optimal conditions, the D-lactic acid yield was 82.15 g/L, which was 32.4% higher than that before optimization (62.01 g/L), and the average optical purity reached 99.89%.